Determination of some heavy metals in canned Sardines fish from Iraqi markets - Jasim, Khalid N.; Shkhaier, Samir L. (Journal of the Faculty of Medicine Baghdad, 2016)
present in the environment could constitute a hazard to food security and public health. These can be accumulated in aquatic animals such as fish. Objective: In this study, selected heavy metals: Copper (Cu), Nickle (Ni), Chromium (Cr) and Iron (Fe) were evaluated in commercial canned fish products (Sardines) that are commonly consumed in Iraq. The canned fish (Sardine) which studied were Yacout Sardine (Morocco), Marina Sardine (Tunisia), Silver Sardine (Morocco) and Salsa Sardine (China). Methods: Prospective study was done in Baghdad from January to June 2016 . 40 samples of four different foreign brands (10 samples for each brand were obtained): Yacout Sardine (Morocco), Marina Sardine(Tunisa), Silver Sardine (Morocco) and Salsa Sardine (China) of canned fish (90 g cans) were analyzed for their content of Cu, Ni, Cr and Fe. Atomic absorption spectroscopy technique was used for determination of metals under study. Results: Mean levels of Cu in four types of canned sardine were 0.7±0.03 μg/g in Yacout canned sardine, 0.9±0.0303 μg/g in Marina canned sardine, 2.1±0.367 μg/g in silver canned sardine and 1.0±0.41 μg/g in Salsa canned sardine, while mean levels of Ni in four samples were 0.14±0.043 μg/g, 0.12±0.035 μg/g ,0.12±0.055 μg/g and 0.14±0.0285 μg/g .Also mean levels of Cr in same four samples were 0.1±0.0332 μg/g, 0.08±0.02 μg/g, 0.1±0.0245 μg/g, 0.11±0.0274 μg/g. and mean levels of Fe in four samples were 21±1.685 μg/g , 25±1.1 μg/g , 20±1.886 μg/g and 30±0.831 μg/g respectively Conclusion: analytical data obtained from this study shows that the metal concentrations for the types of canned sardines except Fe were generally within the Environmental Protection Agency in United States of America (U.S.EPA), Food and Agriculture Organization (FAO),World Health Organization(WHO) and Food and Drug Administration in United States of America (U.S.FDA) recommended limits for canned fish and do not cause any risk for the local consumers, but contamination of Fe in majority of canned sardines samples may cause risk for the consumers.